Effects of laboratory mixing methods and RAP materials on performance of hot recycled asphalt mixtures - Nguyen, Viet Hung (2009)
The primary work reported in this thesis is concerned mainly with the effects of different mixing methods and RAP materials on homogeneity and mechanical properties of hot recycled asphalt mixtures. The recycled asphalt mixture conforms to the requirement of BS 4987-1 (2005) for dense bitumen macadam size 10 mm (DBM 10 mm). The proportion of RAP in the recycled mixture is 40%. RAP materials are artificially aged and processed in the laboratory to prevent the variability of RAP gradation, bitumen content, and the origin. Laboratory RAP is also used to assure that every single RAP particle is an agglomerate of RAP aggregate and binder.